2013
DOI: 10.1016/j.nima.2013.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Muon tomography imaging algorithms for nuclear threat detection inside large volume containers with the Muon Portal detector

Abstract: Muon tomographic visualization techniques try to reconstruct a 3D image as close as possible to the real localization of the objects being probed. Statistical algorithms under test for the reconstruction of muon tomographic images in the Muon Portal Project are here discussed. Autocorrelation analysis and clustering algorithms have been employed within the context of methods based on the Point Of Closest Approach (POCA) reconstruction tool. An iterative method based on the log-likelihood approach was also impl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Using fewer muons provides significant time savings but lower quality images, while a higher number of measured muons results in improved image contrast and resolution but increased measurement time. Existing studies on muon-CT detectors have demonstrated that muons on the order of millions (requiring minutes to days of measurement time, depending on the size and orientation of the detectors) are required for imaging large scale objects such as cargo containers [4,5,11] or dry casks [21][22][23]. Recent work based on simulations showed that several days (>10 6 muons) are needed to identify the location of spent nuclear fuel in dry casks [21][22][23].…”
Section: Cosmic Ray Muon Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Using fewer muons provides significant time savings but lower quality images, while a higher number of measured muons results in improved image contrast and resolution but increased measurement time. Existing studies on muon-CT detectors have demonstrated that muons on the order of millions (requiring minutes to days of measurement time, depending on the size and orientation of the detectors) are required for imaging large scale objects such as cargo containers [4,5,11] or dry casks [21][22][23]. Recent work based on simulations showed that several days (>10 6 muons) are needed to identify the location of spent nuclear fuel in dry casks [21][22][23].…”
Section: Cosmic Ray Muon Tomographymentioning
confidence: 99%
“…This endeavor has been assisted by the development of detectors that can measure and provide information related to the incoming and outgoing trajectories of individual muons [2][3][4][5][6]. Recently, cosmic ray muons have been investigated for volcano imaging [7][8][9] and cargo scanning applications [10][11][12]. Their use has been extended to nuclear waste imaging [13][14][15][16] and determination of nuclear fuel debris location in nuclear reactors having suffered from the effects of a severe accident such as the one that occurred in Fukushima [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The clustering algorithm is a density-based algorithm [11]. It is an improvement of the POCA method, based on a two points correlation analysis.…”
Section: B Reconstruction Algorithmsmentioning
confidence: 99%
“…A considerable amount of simulations and experimental tests on the individual components (scintillators, WLS fibres, photosensors, frontend electronics,...) have been already done. Different reconstruction and visualization algorithms have been implemented and have demonstrated the feasibility of this Project, with several papers reporting specific aspects [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%